Evaluating predictive markers for viral rebound and safety assessment in blood and lumbar fluid during HIV-1 treatment interruption - De Scheerder, Marie-Angélique (J Antimicrob Chemother, 2020)
BACKGROUND: Validated biomarkers to evaluate HIV-1 cure strategies are currently lacking, therefore requiring analytical treatment interruption (ATI) in study participants. Little is known about the safety of ATI and its long-term impact on patient health. OBJECTIVES: ATI safety was assessed and potential biomarkers predicting viral rebound were evaluated. METHODS: PBMCs, plasma and CSF were collected from 11 HIV-1-positive individuals at four different timepoints during ATI (NCT02641756). Total and integrated HIV-1 DNA, cell-associated (CA) HIV-1 RNA transcripts and restriction factor (RF) expression were measured by PCR-based assays. Markers of neuroinflammation and neuronal injury [neurofilament light chain (NFL) and YKL-40 protein] were measured in CSF. Additionally, neopterin, tryptophan and kynurenine were measured, both in plasma and CSF, as markers of immune activation. RESULTS: Total HIV-1 DNA, integrated HIV-1 DNA and CA viral RNA transcripts did not differ pre- and post-ATI. Similarly, no significant NFL or YKL-40 increases in CSF were observed between baseline and viral rebound. Furthermore, markers of immune activation did not increase during ATI. Interestingly, the RFs SLFN11 and APOBEC3G increased after ATI before viral rebound. Similarly, Tat-Rev transcripts were increased preceding viral rebound after interruption. CONCLUSIONS: ATI did not increase viral reservoir size and it did not reveal signs of increased neuronal injury or inflammation, suggesting that these well-monitored ATIs are safe. Elevation of Tat-Rev transcription and induced expression of the RFs SLFN11 and APOBEC3G after ATI, prior to viral rebound, indicates that these factors could be used as potential biomarkers predicting viral rebound.